A reference constructicon as a database - Patel, Malin; Garibyan, Armine; Winckel, Elodie; Evert, Stephanie (Yearbook of the German Cognitive Linguistics Association, 2023)
This article explores the importance of database architecture in building a reference constructicon. Several reference constructicons have been implemented for various languages (FrameNet Constructicon, English Constructicon, Japanese FrameNet Constructicon, German Constructicon, Swedish Constructicon, FrameNet Brasil Constructicon, Russian Constructicon). However, most constructicon projects do not provide explicit information about their implementation or the underlying data model. A recent reference constructicon project dealing mainly with the English language is CASA (Construction Grammar Approach to Syntactic Analysis). In this paper, we present the data model underlying CASA in detail and its current implementation as a relational database and web interface. Relational databases are widely used for many different applications and allow large amounts of data to be stored and managed in a structured and efficient way.<br
Keywords: constructicon; database; Construction Grammar; constructicography; implementation

Arguing one’s way to constructions and constructicons - Herbst, Thomas; Garibyan, Armine (Универсальное и национальное в языковой картине мира : материалы IV Междунар. науч. конф., 2021)
This article aims to outline the basic ideas of constructionist theory. Furthermore, it explores how the meaning of the English WAY construction can be expressed in German or Russian. Finally, it will be shown how Construction Grammar can be used to create a new type of linguistic reference work – a constructicon. <br
Keywords: constructions; Construction Grammar; constructicon; way construction; unpredictability; collo-profiles

Interpreting collocations: An analysis of collocation dictionaries of: English, German and Russian - Garibyan, Armine (Lexicographica, 2019)
Unless online collocation tools have not become common yet, printed collocation dictionaries are still one of the few sources of checking collocative possibilities of a lexical unit. The aim of this paper is to analyse one printed collocation dictionary in each of the 3 languages: English, German and Russian and see which interpretation of collocation was focused on and what user groups were targeted. Also, it was attempted to see whether the morphological specificity of the languages was taken consideration of as compared to the structure of these dictionaries, and further determine whether inclusion or exclusion of certain language-specific information aims at a particular group of target users.<br
Keywords: collocation; dictionary; language-specificity; target user

L2-constructions that go together – more on valency constructions and learner language - Garibyan, Armine; Balog, Evelin; Herbst, Thomas (Yearbook of the German Cognitive Linguistics Association, 2019)
This paper sets out to illustrate differences between learner language and the language of native speakers by a number of tests carried out with students of English at the Friedrich-Alexander-Universität Erlangen-Nürnberg. The first part of the experiment aims at testing knowledge of collocations: In order to compare to what extent combinations of certain words are stored in the constructica of native speakers and advanced learners of English, we used the test battery developed by Dąbrowska (2014): although, as was to be expected, on the whole, native speakers displayed a much greater competence at judging which combinations of words can be regarded as established collocations, interestingly, some learners outperformed some native speakers. The second part of the project was designed to explore the number and types of different valency constructions informants produce on being provided with a verbal stimulus. It is very interesting to see that, given the stimulus word caught, for example, the non-native speakers would predominantly produce sentences with police, thief, murderer, suspect etc. which do not rank amongst the 50 top collexemes of caught in the British National Corpus. We would thus argue that an analysis of the words used in particular slots of argument structure constructions (i.e. the collexemes or itecxes) provides a useful means of characterizing the language of advanced learners and to underscore the importance of collo-phenomena in language teachin
Keywords: collocation; construction; pattern; valency; learner language

Neural correlates of linguistic collocations during continuous speech perception - Garibyan, Armine; Schilling, Achim; Boehm, Claudia; Zankl, Alexandra; Krauß, Patrick (Frontiers in Psychology, 2022)
Language is fundamentally predictable, both on a higher schematic level as well as low-level lexical items. Regarding predictability on a lexical level, collocations are frequent co-occurrences of words that are often characterized by high strength of association. So far, psycho- and neurolinguistic studies have mostly employed highly artificial experimental paradigms in the investigation of collocations by focusing on the processing of single words or isolated sentences. In contrast, here we analyze EEG brain responses recorded during stimulation with continuous speech, i.e., audio books. We find that the N400 response to collocations is significantly different from that of non-collocations, whereas the effect varies with respect to cortical region (anterior/posterior) and laterality (left/right). Our results are in line with studies using continuous speech, and they mostly contradict those using artificial paradigms and stimuli. To the best of our knowledge, this is the first neurolinguistic study on collocations using continuous speech stimulation.
CRIS-Team WoS Importer:2023-01-27

Strategies of fair lexicography - how present- day dictionaries of English show respect - Garibyan, Armine; Koroleva, Daria; Mittmann, Brigitta; Herbst, Thomas (Lexicographica, 2022)
This article investigates the ways in which present-day monolingual dictionaries of the English language show respect towards groups of people. On the basis of the analysis of selected entries of the most recent editions of English learners' dictionaries and the Concise Oxford Dictionary we outline five different strategies employed in these dictionaries to avoid discrimination of and offensiveness towards other people. The analysis comprises the phrasing of definitions, illustrations, the selection of examples, the choice of headwords as well as usage notes in comparison to data obtained from English corpora.
CRIS-Team WoS Importer:2022-12-30